Analysis of Rate of Change of Strength in Elite Class Indian Judokas with Respect to Anthropometric Variables: The Impact of Anthropometric Variables on the Rate of Change in Strength of Elite Indian Judokas (Journal of Advances and Scholarly Researches in Allied Education, 2023)
The present study was conducted in an attempt to quantify the rate of change of muscularstrength with respect to 1 unit change in circumference of that particular group of muscle. To achieve theobjectives of the study 52 Judokas were recruited to the study of age 22±3.21y. Judokas with training age≥5 years, had experience of playing at national level tournaments and above took part in the studyvoluntarily. Subjects performance was tested on 2 strength variables (bench press and leg strength), and3 anthropometric variables (chest circumference, thigh circumference, and calf circumference).Regression analysis was used as statistical tool for computation the data. Level of significance was setat 0.05 for whole analysis. Results of the analysis suggests that predictor variable chest circumferencealone is capable of explaining 71 change in performance of bench press. In another multiple regressionanalysis it was noted that 89 change in performance of leg strength can be claimed by twoanthropometric variables namely thigh circumference, and calf circumference.